2012
DOI: 10.1128/jb.00958-12
|View full text |Cite
|
Sign up to set email alerts
|

The Primosomal Protein DnaD Inhibits Cooperative DNA Binding by the Replication Initiator DnaA in Bacillus subtilis

Abstract: DnaA is an AAA؉ ATPase and the conserved replication initiator in bacteria. Bacteria control the timing of replication initiation by regulating the activity of DnaA. DnaA binds to multiple sites in the origin of replication (oriC) and is required for recruitment of proteins needed to load the replicative helicase. DnaA also binds to other chromosomal regions and functions as a transcription factor at some of these sites. Bacillus subtilis DnaD is needed during replication initiation for assembly of the replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…Residues in this region of DnaA have also been implicated as possible sites of interaction with YabA and DnaD (Cho et al ., ; Scholefield and Murray, )(Fig. ), two other DnaA regulators that can also inhibit DnaA oligomerization (Bonilla and Grossman, ; Scholefield and Murray, ). It is feasible that if Soj targets this surface of DnaA, then substitutions that change the Soj‐DnaA interaction might also affect DnaD and YabA binding, leading to overreplication.…”
Section: Discussionmentioning
confidence: 99%
“…Residues in this region of DnaA have also been implicated as possible sites of interaction with YabA and DnaD (Cho et al ., ; Scholefield and Murray, )(Fig. ), two other DnaA regulators that can also inhibit DnaA oligomerization (Bonilla and Grossman, ; Scholefield and Murray, ). It is feasible that if Soj targets this surface of DnaA, then substitutions that change the Soj‐DnaA interaction might also affect DnaD and YabA binding, leading to overreplication.…”
Section: Discussionmentioning
confidence: 99%
“…We then utilized one of these DnaA variants to show that YabA specifically inhibits DnaA helix formation in vitro . Moreover, based on the striking similarity of our results here regarding YabA, our previously reported results regarding Soj (Scholefield et al ., ), and a recent report regarding DnaD (Bonilla and Grossman, ), we have gone on to show that DnaD also inhibits DnaA helix formation in vitro . Taken together, these results indicate that all of the known regulators of B. subtilis DnaA present during vegetative growth specifically target DnaA helix formation during the initiation reaction.…”
Section: Introductionmentioning
confidence: 90%
“…It was recently indicated that the means of regulating replication initiation through YabA protein and pri mosome protein DnaS are similar by the mechanism. They both decrease the cooperativity of binding of DnaA with OriC and do not influence the ability of DnaA to bind or hydrolyze ATP [71,78].…”
Section: On the Mechanisms Of Replication Initiation In Bacteria In Lmentioning
confidence: 99%
“…Each of these mechanisms, according to our studies [43,44], is able to coordinate growth and replication in the cell by exponential type. These are the mechanisms regulat ing the DNA replication initiation process by YabA [70], DnaD [71], Soj [72], Spo0A, and SirA [5,[73][74][75][76] proteins. It is noteworthy that soj and yabA genes in B. subtilis are located near OriC, which is also in accordance with the mechanism of coordinating growth and replication suggested in the model [20].…”
Section: On the Mechanisms Of Replication Initiation In Bacteria In Lmentioning
confidence: 99%